Handbook for social workers on basic bio-psychosocial help for children in need of special protection - De Castro, Elizabeth Protacio (Center for Integrative and Development Studies. University of the Philippines, 2001)
This book aims to introduce the social workers to children in need of special protection (CNSP) and bio-psychosocial help. It contains guidelines, tool and techniques in helping CNSP. It was published so that social workers will become more efficient and effective in handling cases of CNSP.